The Effect of Lower-Body Blood Flow Restriction on Static and Perturbated Stable Stand in Young, Healthy Adults - Willberg, Christina; Zentgraf, Karen; Behringer, Michael (Frontiers in Human Neuroscience, 2021)
Muscular fatigue can affect postural control processes by impacting on the neuromuscular and somatosensory system. It is assumed that this leads to an increased risk of injury, especially in sports such as alpine skiing that expose the body to strong and rapidly changing external forces. In this context, posture constraints and contraction-related muscular pressure may lead to muscular deoxygenation. This study investigates whether these constraints and pressure affect static and dynamic postural control. To simulate impaired blood flow in sports within a laboratory task, oxygen saturation was manipulated locally by using an inflatable cuff to induce blood flow restriction (BFR). Twenty-three subjects were asked to stand on a perturbatable platform used to assess postural-related movements. Using a 2 × 2 within-subject design, each participant performed postural control tasks both with and without BFR. BFR resulted in lower oxygenation of the m. quadriceps femoris (p = 0.024) and was associated with a significantly lower time to exhaustion (TTE) compared to the non-restricted condition [F(1,19) = 16.22, p < 0.001, ηp2 = 0.46]. Perturbation resulted in a significantly increased TTE [F(1,19) = 7.28, p = 0.014, ηp2 = 0.277]. There were no significant effects on static and dynamic postural control within the saturation conditions. The present data indicate that BFR conditions leads to deoxygenation and a reduced TTE. Postural control and the ability to regain stability after perturbation were not affected within this investigation.